2016
DOI: 10.1007/s11999-015-4583-4
|View full text |Cite
|
Sign up to set email alerts
|

Does Early versus Delayed Spanning External Fixation Impact Complication Rates for High-energy Tibial Plateau and Plafond Fractures?

Abstract: Background High-energy tibial plateau and tibial plafond fractures have a high complication rate and are frequently treated with a staged approach of spanning external fixation followed by definitive internal fixation after resolution of soft tissue swelling. A theoretical advantage to early spanning external fixation is that earlier fracture stabilization could prevent further soft tissue damage and potentially reduce the occurrence of subsequent infection. However, the relative urgency of applying the extern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 16 publications
0
29
0
1
Order By: Relevance
“…It has also shown by some to increase the chance of infection. 20,21 The fixation method presently being studied, however, combines the benefits of minimal soft tissue trauma, and adequate stabilization of the fracture so that mobilization may be begun soon after surgery and the patient well rehabilitated in the process. Hybrid fixators are also valuable when the articular fragment is small and unsuitable for internal fixation with plates and screws.…”
Section: Discussionmentioning
confidence: 99%
“…It has also shown by some to increase the chance of infection. 20,21 The fixation method presently being studied, however, combines the benefits of minimal soft tissue trauma, and adequate stabilization of the fracture so that mobilization may be begun soon after surgery and the patient well rehabilitated in the process. Hybrid fixators are also valuable when the articular fragment is small and unsuitable for internal fixation with plates and screws.…”
Section: Discussionmentioning
confidence: 99%
“…, which were described in nine studies[22,32,43,48,50,51,53,60,62]. There was no significant heterogeneity between these studies.…”
mentioning
confidence: 99%
“…As the injury increases, the ankle joint Varus and the medial column injury is more serious than the lateral column. And JustinM [21] also found that the proper xation of the medial column reduces the risk of nonunion after pilon fracture. Based on the principle of early functional exercise, the strong xation of the medial column becomes more and more important.…”
Section: Discussionmentioning
confidence: 96%